LEADERSHIP STRUCTURE AND GROUP DYNAMICS IN THE MILITARY - Mabia, Chidozie E; Nweke, Kingsley O (Practicum Psychologia, 2018)
The military is a highly structured group; hence order and roles are strict and clear. The head of the armed forces is the commander-in-chief (CIC), who is the president in Nigeria. Three arms of the military in Nigeria have the organogram in accordance with perceived needs, and in line with international practice. Officers and men of the Nigerian army are classified into two major categories of commissioned and non-commissioned officers, and these have their own hierarchies. The Nigerian army has five commands and five autonomous units, while the air force has five principal staff branches. Maintenance of order in the military, and promotion of efficiency imposes psychological tasks on military psychologists in all units and formations of the military in Nigeria.